Hubungan antara belanja pemerintah, tingkat kemiskinan, dan pertumbuhan ekonomi daerah otonomi baru di Provinsi Lampung - Ambya, Ambya; Ciptawaty, Ukhti (Jurnal Paradigma Ekonomika, 2022)
The application of Partial Least Square (PLS) for causal modeling has been widely used in many fields of study, especially in economics. This paper will use PLS analysis to be applied to a model testing the relationship between variables: government spending, poverty level, and economic growth. The results of the analysis show that there is an indirect effect of education (education spending) on ​​poverty of -0.509 and health spending on poverty with an effect of -0.510, parameter estimates and significant significance; There is an effect of total poverty on GRDP of -0.983, with a very significant and significant parameter estimate. Applications, it is urgency to build an analysis to find out how the relationship between government spending, poverty levels, and economic growth. This analysis will help better understand how government budget allocations can affect poverty levels, so far poverty levels ultimately affect economic growth in new autonomous regions in Lampung.